The Effect of China and America's Economic Uncertainty on the Performance of the High Dividend 20 Index - Lestari, Novi Puji; Rahadjeng, Erna Retna (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the effect of Global Uncertainty in China and the United States on the High Dividend 20 Index. The data used in this study are time series financial report data for the period January - December 2021-2023. The research model used is Vector Auto Regressive (VAR). VAR is usually used to analyze the relationship of time series variable systems and to analyze the impact of disturbance factors on variable systems and one of which is global uncertainty. The results show that in the short term the US EPU affects the High Dividend 20 Index. The variable that has no effect in the short term is China EPU. Meanwhile, in the long term, China EPU and US EPU have no effect. Based on the control variables used in the short and long term, the Inflation and Export variables significantly affect the High Deviden 20 Index.